Estimativa de riqueza de macroinvertebrados bentônicos e a relação da composição de comunidades com componentes de meso-habitat em riachos de cabeceira no cerrado - Deborah Regina de Oliveira e Silva (2012)
Headwater streams are important components of a watershed and harbor a high diversity of benthic macroinvertebrates. The study of composition and structure of these organisms and their relationship with the environment in which they live provides an important tool for biodiversity conservation. The aim of the first chapter was to assess regional and local scales in the sampling effort using the second order Jackknife for richness estimation. The results showed that regionally, there was a significant percentage of the estimated richness (93% for families and 82% for Ephemeroptera, Plecoptera and Trichoptera - EPT). Locally, however, the median rate was 68% to 65% for families and EPT, respectively. A higher sampling effort should be employed to cover most of the total macroinvertebrate richness at the local scale. The second chapter aims to assess how much of the distribution of benthic macroinvertebrate community can be explained by environmental factors of meso-habitat (substrate types and flows) and the variation between streams, using the method of variance partitioning. The percentage of variation in biological communities explained by environmental factors was higher compared to the explanation given by the variation between streams (32% for abundance and 23% for presence-absence of the total community; and 30% for abundance and 24% for presence-absence of EPT assemblages). Regarding the importance of substrates and flows as meso-habitat components it was observed that flow types accounted for more than 60% of environmental variation for both the total community and for EPT assemblages. The results highlighted that the interaction between hydrological and geomorphological conditions affect benthic macroinvertebrate communities and that their arrangement is important at the meso-scale in headwater streams at cerrado